PENGARUH KUALITAS PELAYANAN PEMBELIAN MOTOR YAMAHA DALAM UPAYA MENINGKATKAN KEPUASAN KONSUMEN PADA USAHA DAGANG (UD) MAJU KENDARI - Niskawati, Niskawati; kambolong, makmur; nurjannah, nurjannah (Universitas Halu Oleo, 2016)
This study aims to determine the Quality of Service Purchase of Yamaha Motor has an effect on increasing customer satisfaction at UD Maju Kendari. The type of data used in this study is in the form of a questionnaire and an interview. The results of the analysis in this discussion are analyzed using inferential statistical analysis. Because the number of independent variables in this study is only one variable, namely Customer Satisfaction as the X variable and the dependent variable as the Y variable, then testing the relationship between variables is used Simple Correlation Analysis (Pearson Product Moment). Which has an Average of (4.44) which is categorized as